New insight on the enteric cholinergic innervation of the pig colon by central and peripheral nervous systems: reduction by repeated loperamide administration - Yuan, Pu-Qing; Li, Tao; Million, Mulugeta; Larauche, Muriel; Atmani, Karim; Bellier, Jean-Pierre; Taché, Yvette (Frontiers in Neuroscience, 2023)
The central and peripheral nervous systems provide cholinergic innervation in the colon. The ability to assess their neuroanatomical distinctions is a challenge. The pig is regarded as a translational model due to the close similarity of its enteric nervous system (ENS) with that of human. Opioid-induced constipation is one of the most common sides effects of opioid therapy. We developed an approach to differentiate central and peripheral cholinergic innervation of the pig colon using double immunolabeling with a novel mouse anti-human peripheral type of choline acetyltransferase (hpChAT) antibody combined with a rabbit anti-common type of ChAT (cChAT) antibody, a marker of cholinergic neurons in the central nervous system. We examined their spatial configuration in 3D images of the ENS generated from CLARITY-cleared colonic segments and their density was quantitated computationally using Imaris 9.7. Changes in the distal colon induced by daily oral µ opioid receptor agonist, loperamide (0.4 or 3 mg/kg, 4 weeks) were assessed. The double labeling showed strong cChAT immunoreactive (ir) fibers in the cervical vagus nerve and neuronal somata and fibers in the ventral horn of the sacral (S2) cord while hpChAT-ir was visualized only in the ENS but not in the vagus or sacral neural structures. In the colonic myenteric plexus, hpChAT-ir neurons and fibers and varicose cChAT-ir fibers surrounding hpChAT-ir neurons were simultaneously visualized in 3D. The density of cChAT-ir varicose fibers in the outer submucosal plexus (OSP) were higher in the transverse and distal colon than in the proximal and in the myenteric plexus (MP) compared to the OSP. There is no cChAT innervation in the inner submucosal plexus. The density of hpChAT in the ENS showed no segmental or plexuses differences. Loperamide at the highest dose decreased significantly the density hpChAT-ir fibers + somata in the MP of the distal colon. These data showed in 3D the distinct density of central cholinergic innervation between myenteric and submucosal plexuses among colonic segments and the localization of cChAT-ir fibers around peripheral hpChAT neurons. The reduction of cholinergic myenteric innervation by chronic opiate treatment points to target altered prokinetic cholinergic pathway to counteract opiate constipation.